On the micro-foundations of contract versus conflict with implications for international peace-making - José A. Cuesta; Syed Mansoob Murshed (Inter-American Development Bank, Research Department, 2008)
This paper expands the micro-foundations of the traditional greed and grievance non-cooperative model of civil conflict between a government and a rebel group. First, the paper's model allows for greed and grievance to be orthogonal, so that they may affect each other. Second, the model allows for the reaction curves of both parties in non-cooperative games to be substitutes and not inevitably complementary. Third, the paper allows for Diaspora transfers to rebel groups. Fourth, the paper expands external aid in the form of fungible financing of government transfers 'buying' peace. These extensions provide a better understanding of conflict persistence, the consequences of competing international aid and why sub-optimal sanctions provision ('cheap talk') by the international community are frequent.
Keywords: C78; D72; D74; D83; 330; Civil war; Social contract; Aid for peace